Effectiveness and Challenges of Task-Based Language Teaching on the Speaking Proficiency of Vietnamese ESL Learners - August Jay C. Rufo (Researchparks Publishing, 2026)
This study evaluated the effectiveness of the Task-Based Language Teaching (TBLT) and explored the institutional and pedagogical variables that affect its implementation in improving the speaking skill of the learners of English as a second language in the Vietnamese context. The study looked at how TBLT can contribute towards fluency, accuracy, and overall holistic communicative competence in Vietnamese classrooms that are inherently oriented to teacher-centred pedagogy, and so overcome the long-standing gap between formal English instruction and the ability of learners to participate in real-life communicative purposes. The study also corresponds to SDG 4 (Quality Education) and 2040 targets of the Ambisyon Naten by supporting the presence of a learner-centered and dialogic pedagogical paradigm. To outline the connections between the degree of TBLT implementation and oral proficiency of the participants, a quantitative descriptive -correlational design was used. The information was gathered through performance assessment in the form of speaking, a written questionnaire, and a classroom evaluation rubric. The statistical processes involved frequency distributions, percentage, means, standard deviations, and inferential tests including the Mann Whitney U and Friedman tests to question the correlation between the TBLT exposure and speaking performance including fluency, cohesion, and phonological accuracy. The findings revealed a strong and statistically significant correlation between TBLT exposure and speaking proficiency and thus ensuring that increased involvement in task-based undertakings produce better oral communicative performance. However, the research found the presence of salient limitations, such as the insufficient teaching time, large enrolments, and teacher preparation, and they are all relevant to emphasize the need to support teaching and professional development with institutional support.